Photolithographic strategy for patterning preformed, chemically modified, porous silicon photonic crystal using click chemistry - Zhu, Y.; Gupta, B.; Guan, B.; Ciampi, Simone; Reece, P.; Gooding, J. (American Chemical Society, 2013)
Porous silicon (PSi) is an ideal platform for label-free biosensing, and the development of porous silicon patterning will open a pathway to the development of highly parallel PSi biochips for detecting multiple analytes. The optical response of PSi photonic crystal is determined by the changes in the effective bulk refractive index resulting from reactions/events occurring within the internal pore space. Therefore, introducing precise chemical functionalities in the pores of PSi is essential to ensure device selectivity. Here we describe the fabrication of PSi patterns that possess discrete chemical functionalities that are restricted to precise locations. The key difference to previous patterning protocols for PSi is that the entire porous material is first modified with a self-assembled monolayer of a α,ω-diyne adsorbate prior to patterning using a microfabricated titanium mask. The distal alkyne moieties in the monolayer are then amenable to further selective modification by the archetypal “click” reaction, the copper catalyzed alkyne–azide cycloaddition (CuAAC), using the titanium mask as a resist. This type of patterning is suitable for further immobilization of biological recognition elements, and presents a new platform for highly parallel PSi biosensor for multiple detections.